AFFIRMATIVE ENFORCEMENT FOR MICRO, SMALL, AND MEDIUM ENTERPRISES IN THE FIELD OF INTELLECTUAL PROPERTY RELATED TO NATURAL COLOURS IN BATIK MAKING - Yustiana Dwirainaningsih; Dheasari Rachdantia; Mursidah; Andri Nur Cahyo (Bengkoelen Justice : Jurnal Ilmu Hukum, 2024)
The importance of Intellectual Property Rights protection for Micro, Small and Medium Enterprises is a major highlight in supporting the sustainability and economic competitiveness of this sector. IPR has great potential to add value to the products and services produced by MSMEs, create a competitive advantage, and protect innovations or brands from the threat of infringement. However, various obstacles such as complex administrative procedures, high costs, unsupportive regulations, and limited law enforcement related to IPR violations are significant challenges for MSME actors. Normative legal research in this context aims to identify solutions to these problems, through simplification of the registration process ensuring that IPR registration procedures are simpler and more accessible to MSME actors subsidising registration fees providing relief from IPR registration fees through government subsidies or fiscal incentives for MSMEs that register their IPRs improvement of regulations encourages revision of regulations that pay attention to the needs of MSMEs, such as accelerating the time of the registration process and recognition of IPRs for local or traditional typical products. Increased law enforcement encourages revision of regulations that pay attention to the needs of MSMEs, such as accelerating the time of the registration process and IPR recognition for local or traditional typical products. Socialisation and education are expected to educate MSME players about the strategic benefits of IPR and how to take advantage of the system to support their businesses. Policies that support MSMEs are more optimal in utilising IPR to increase competitiveness, open up opportunities for market expansion, and protect local innovation and creativity. Collaborative efforts between the government, related institutions, and MSME players are the key to the optimal use of IPR. Keywords: MSMEs natural color batik, Affirmative, Intellectual Property